Nutrition Status of Class XI Students of State Senior High School 1 Tembilahan City - Irna Lia Mawita; khairuddin khairuddin (Jurnal Olahraga Indragiri, 2023)
The problem of this research is that the students of SMA Negeri 1 Tembilahan Kota easily experience fatigue, slow movement, lack of enthusiasm, lack of enthusiasm for learning and other things. The purpose of this research was to determine the nutritional status of SMA Negeri 1 Tembilahan Kota. The population in this study were all 16 students of class XI MIPA 3. while the sampling in this study used a purposive sampling technique with the condition that the sample was homogeneous or similar, in this case all students of class XI MIPA 3 were taken. data analysis agency using a percentage descriptive formula then performs data analysis with a qualitative descriptive with percentages. The results of the analysis show that (F) the frequency of the total value is 298.29, and for the number (N) the maximum overall score is 507.52. So to get a percentage or (P) total (F) 298.29 divided by (N) 507.52 multiplied by 100%, then the percentage result is 58.77%. Thus it can be concluded that the nutritional status of SMA Negeri 1 Tembilahan students belongs to the "less" category because it lies in the interval of 55% - 64%.